2019
DOI: 10.1038/s41467-019-13260-9
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic gamma stimulation rescues memory impairments in an Alzheimer’s disease mouse model

Abstract: Slow gamma oscillations (30–60 Hz) correlate with retrieval of spatial memory. Altered slow gamma oscillations have been observed in Alzheimer’s disease. Here, we use the J20-APP AD mouse model that displays spatial memory loss as well as reduced slow gamma amplitude and phase-amplitude coupling to theta oscillations phase. To restore gamma oscillations in the hippocampus, we used optogenetics to activate medial septal parvalbumin neurons at different frequencies. We show that optogenetic stimulation of parval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 70 publications
7
179
0
Order By: Relevance
“…These results show that AD mice, despite showing aberrant brain dynamics (state 4) at baseline, may return to wild-type-like brain dynamics following theta rhythm optogenetic stimulation of EC. This complements previous evidence that EC stimulation may provide therapeutic benefit in AD 38 , and provides causal evidence of a mechanism that might underpin clinical benefits of EC stimulation.…”
Section: Impaired Multiplexing In Brain Network Dynamics In a Transgesupporting
confidence: 82%
“…These results show that AD mice, despite showing aberrant brain dynamics (state 4) at baseline, may return to wild-type-like brain dynamics following theta rhythm optogenetic stimulation of EC. This complements previous evidence that EC stimulation may provide therapeutic benefit in AD 38 , and provides causal evidence of a mechanism that might underpin clinical benefits of EC stimulation.…”
Section: Impaired Multiplexing In Brain Network Dynamics In a Transgesupporting
confidence: 82%
“…Other studies showed that alteration gamma with anxiety behaviors (Batashvili et al, 2019;Cruces-Solis et al, 2019;Zhou et al, 2018). Nevertheless, to our knowledge, there is no study showing a systematic effect of aging on magnitude of gamma power, except when degeneration is present (Etter et al, 2019;Goutagny et al, 2013). The lack of theta2 in animals treated with 5-MeO-DMT associated to the lack of anxiety-like behavior also suggest that lack of anxiety rather than aging explain the absence of theta2 in old animals.…”
Section: Discussionmentioning
confidence: 80%
“…It would be crucial in the future to determine whether optogenetic stimulation of BF PV+ neurons could also modify cognitive functions. A recent study showed that the acute optogenetic induction of low gamma oscillations (but not high gamma) in the hippocampus can rescue memory impairments 26 . Although we did not observe any significant changes in plaque density in the hippocampus, hippocampus-dependent functions may be modified through the modulation of septal activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased or decreased neural firing promotes or suppresses the spread of Amyloid-β (Aβ), respectively 22 , 23 . In particular, the artificial induction of cortical gamma oscillations is an attractive option because it can reduce amyloid load and improve cognitive functions by activating microglia 10 , 11 , 24 , 25 and because optogenetic restoration of hippocampal gamma oscillations can rescue memory impairments 26 .…”
Section: Introductionmentioning
confidence: 99%